Development of Digital Modules for Gamification-Based Measurement Materials through MOOCs Platforms to Improve Learning Motivation and Learning Outcomes of Class X High School Students - Herlambang, Arthur Muhamad Taufan; Risdianto, Eko; Setiawan, Iwan (Asian Journal of Science Education, 2025)
The purpose of this study is to determine the feasibility of developing digital modules, to find out students responses to digital modules, and to find out students learning motivation after using gamification-based digital modules through the MOOCs platform. This study uses the Research and Development (RD) method using the ADDIE model. As a result of the interview, students in Bengkulu stated that they felt bored and had difficulty understanding the physics learning taught by the teacher. The subjects used were thirty-four students of class XA MAN 2 Bengkulu City and one teacher. Research data was obtained through expert validation sheets, student response questionnaires, student learning motivation questionnaires and pretest-posttests to measure student learning outcomes that were analyzed qualitatively and quantitatively. The results of the validation of the digital module as a whole were obtained with a percentage of 95% which was included in the very feasible category, 94% of the validation of media questions which showed the category was very feasible, 80% of student responses which showed the category was very good, there was an increase in learning motivation with a moderate category with an N-Gain result of 0.43, and there was an increase in learning outcomes with a medium category with an N-Gain result of 0.52.